The partnership theory in explaining cooperatives organizational structure - Zelhuda, Shamsuddin; Abdul Ghafar, Ismail (Medwell Journals, 2016)
This study discusses the application of the partnership theory within the structure of cooperative organizations. A cooperative organization is established from the capital contributed by its members and thus, it directly creates a partnership alliance among them. Partnership and cooperation perspectives represent the structure of the cooperatives in general. As cooperative activities contribute a substantial share to the development of the economy, cooperatives experience rapid growth. However, not all members tend to be committed to the management of cooperatives. This has led cooperatives to experience a number of agency issues such as opportunism action by the member or partner and the manager employed.